Perpendicular magnetocrystalline anisotropy energy (MAE) of 111-surface slab of Fe2CoAl. (5th June 2020) - Lalrinkima,; Fomin, L A; Malikov, I V; Zadeng, Lalthakimi; Rai, D P
Abstract: We have analyzed the surface stability of different orientations(111, 001, 011) of Fe2 CoAl (FCA) slabs. Among all the slabs, the orientation with 111-surface is found to be most stable with minimum energy. The surface electronic and magnetic properties along with the atomic orbital resolved magnetocrystalline anisotropy energy (MAE) has been performed by using first principles density functional theory (DFT). We have reported the surface metallicity with dispersed electronic bands around the fermi energy (E F ) in all the three terminals Fe/Co/Al. This may be the result of translational broken symmetry in which metallic bonds are broken with the release of free conducting electrons on the surface. We have observed the presence of both the in-plane MAE and the out-plane MAE characterized by the distribution of total MAE over an atomic sites for each Al-, Co- and Fe-terminal. The total MAE favors in-plane magnetization in case of antiferromagnetic configured Al-terminal (MAE = 0.034 meV) and Fe-terminal (0.68 meV) whereas out-plane total MAE is observed in ferromagnetic configured Co-terminal.